(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
The contract is exposed to numerous circumstances and variables, whether financial, economic, or even political, which have repercussions resulting in contractual imbalance liable to cause economic disruptions for the contracting parties during the execution phase, especially in the context of electronic commercial contracts due to their digital and international nature. Hence, this study delves into the economic impacts encountered by the contract, thus seeking the legal mechanisms outlined by the legislator to address these unforeseen circumstances, thereby safeguarding contractual equilibrium so that the parties can execute the contract fairly for both sides. It is at this juncture that the theory of unforeseeability assume paramount importance, offering significant solutions, notably following their evolution on the legal and judicial fronts.